2018
DOI: 10.1089/jpm.2017.0054
|View full text |Cite
|
Sign up to set email alerts
|

Parenting in Childhood Life-Threatening Illness: A Mixed-Methods Study

Abstract: Future research can further examine trade-offs and associated effects, how to support parent problem-solving and decision-making around trade-offs, and how to best offer social services alongside illness-directed care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 65 publications
5
59
0
Order By: Relevance
“…24 In addition, parents expressed angst over their role of being a parent to multiple children. Parents feel pulled between two fronts and describe this as, “no one is getting what they need and won’t be for a while.” 7 Parents may have goals for themselves in caring for all of their children they are unable to meet because demands on their time and energy are numerous or intense.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In addition, parents expressed angst over their role of being a parent to multiple children. Parents feel pulled between two fronts and describe this as, “no one is getting what they need and won’t be for a while.” 7 Parents may have goals for themselves in caring for all of their children they are unable to meet because demands on their time and energy are numerous or intense.…”
Section: Resultsmentioning
confidence: 99%
“…Parents have described a process of trading-off the needs of one family member in order to meet the needs of another while caring for a seriously ill child. 7 Understanding how the concept of moral distress applies to families of seriously ill children can inform how providers undertake discussions on goals of care and collaborate with families and how ethics consultants approach conflicts between families and healthcare providers that arise in the day-to-day care of these children. Therefore, we present the results of our dimensional analysis review to answer the question, “What is the nature of parent moral distress in serious pediatric illness?…”
Section: Introductionmentioning
confidence: 99%
“…The nursing shortage translates into a lived experience for families with children with complex medical conditions through employment, economic, emotional, and psychosocial impact. 34 …”
Section: Discussionmentioning
confidence: 99%
“…This finding is congruent with our research. Authoritarian style is a part of overparenting, which comprises two related aspects of over-controlling and overprotection (16). Furthermore, previous studies have found that over-controlling parents are more prone to depression and overprotective parents are more prone to anxiety (17).…”
Section: Discussionmentioning
confidence: 99%